Intensive Arabic Language Teaching to Acquire the Four Linguistic Skills | Tadrĩs al-Lugah al-‘Arabiyyah al-Mukaśśaf li Iktisāb al-Mahārāt al-Lugawiyyah al-Arba’ - Ihwan, Muhamad Bisri; Himmah, Ro’fat Hizmatul; Rasyidi, Abdul Wahab; Al Fatih, Muhamad Fai (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to find out how the application of intensive Arabic learning at the Islamic Boarding School for Girls Minhajut Thullab Muncar Banyuwangi. This intensive learning is expected by students to be able to understand four skills in Arabic. Also to identify strengths and weaknesses in intensive Arabic learning. To obtain data, researchers used a qualitative research approach using types of fields, the source of research data was purposive sampling to students at the Islamic Boarding School. While the data collection methods used in this study were observation in the Islamic Boarding School Environment, interviews with Caregivers, the Arabic language teachers in the Islamic Boarding School and documentation during intensive learning took place, for the validity of this study using data triangulation. data sources and theories. The results of this study that 1) implementation of intensive Arabic learning to gain some skills at Islamic Boarding School for Girls Minhajut Thullab Muncar Banyuwangi can improve language skills, 2) strengths and weaknesses in the application of intensive learning. The learning system has the advantage of being able to further enhance some skills, ranging from proficiency in listening, reading, speaking, and writing in Arabic for students, but also has many drawbacks similar to that some Arabic lessons are less able students with good control and the teacher cannot monitor the full implementation of Arabic students in speaking every day.